2016
DOI: 10.1074/jbc.m115.698613
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Enhanced Activity in Factor VIIa-Trypsin Variants Conveys Insights into Tissue Factor-mediated Allosteric Regulation of Factor VIIa Activity

Abstract: The complex of coagulation factor VIIa (FVIIa), a trypsin-like serine protease, and membrane-bound tissue factor (TF) initiates blood coagulation upon vascular injury. Binding of TF to FVIIa promotes allosteric conformational changes in the FVIIa protease domain and improves its catalytic properties. Extensive studies have revealed two putative pathways for this allosteric communication. Here we provide further details of this allosteric communication by investigating FVIIa loop swap variants containing the 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 57 publications
4
26
0
Order By: Relevance
“…These results indicate that the delay in time to peak observed for chimeric FX-C in the TG assays reflects the additional time that is required by FX-C to engage FVa and become fully active. Importantly, studies on the protease–zymogen equilibrium of trypsin-like proteases have shown that the S4 subsite is involved in stabilization of the protease state 29 , 39 , 40 . As the 99-loop is allosterically linked to the S4 subsite, insertions within the 99-loop may indeed shift the protease equilibrium toward a more zymogen-like state in the chimeric FXa variants.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the delay in time to peak observed for chimeric FX-C in the TG assays reflects the additional time that is required by FX-C to engage FVa and become fully active. Importantly, studies on the protease–zymogen equilibrium of trypsin-like proteases have shown that the S4 subsite is involved in stabilization of the protease state 29 , 39 , 40 . As the 99-loop is allosterically linked to the S4 subsite, insertions within the 99-loop may indeed shift the protease equilibrium toward a more zymogen-like state in the chimeric FXa variants.…”
Section: Resultsmentioning
confidence: 99%
“…Pm‐FVIIa with a four‐residue shorter 170‐loop compared with human shows reduced structural change in the 170‐loop that increases in Pm‐sTf/FVIIa compared with human. We do not see skewing of the final TF‐binding helix turn as described for Hu‐FVIIa IIa . These points, together with the finding that truncation alone reduced intrinsic FVIIa activity, makes explanation of the contributions of smaller 170‐loop size and/or the specific interactions of trypsin‐like 170‐loop residues to activity enhancement and comparisons with Pm‐FVIIa activity unclear.…”
mentioning
confidence: 45%
“…Nonetheless, previous MD studies using Hu‐FVIIa structure and a Hu‐sTF/FVIIa model computationally generated from combined experimental structures have demonstrated that components of sTF‐mediated allosteric activation of Hu‐FVIIa include significant stabilization and reduced flexibility of the protease domain, in particular the TF‐binding helix, 170‐loop, 94‐shunt, and activation loop3 and loop1 . Additional identified sTF‐effects on FVIIa included stabilized, reduced exposure of W364 and reductions in Cβ distances between the TF‐binding helix/170‐loop region and activation loop3 or loop2 residues, and between loop1 and loop3 residues .…”
mentioning
confidence: 99%
“…Observation 4: Shortening of the 170-loop by grafting the trypsin loop into h-FVIIa seems to affect the structural integrity of the TF-binding helix and enhances activity [14][15][16]. We and others have shown that shortening of the 170-loop ( Fig.…”
mentioning
confidence: 88%
“…Observation 5: The combination of sequence elements (mutations and grafts) that modulate protease activity and TF-induced allostery, in particular those mentioned in Observations 1-4 above, generally produces expected additive effects, albeit with some possibility of synergy [7,9,13,15,16]. This combination heuristic is supported by biochemical evidence whose finer nuances are addressed in the cited articles.…”
mentioning
confidence: 88%